ASSOCIATED THERAPIES FOR ACNE SCARS ATTENTION: A LITERATURE REVIEW - Barros da Cruz Brito, Mayara; Carolina Marques de Oliveira, Adna; Nunes Dantas, Ivanilda; de Freitas Lima, Rennaly; Galindo de Oliveira, Janaina; Gomes Moreira, Andréia (Health and Society, 2022)
Acne scars are a frequent complication with major social and psychological implications for the individual, to which attention must be paid. aiming at the timely and aggressive management of severe forms of acne, thus avoiding, as far as possible, its appearance. However, some of these patients will present this complication even with early intervention, this is due to impaired healing and the severity and duration of the inflammatory phenomenon. At a time when there are still no indisputable treatments in this area, it is necessary to seek a consensus that allows patients to provide physical and psychological relief for an irreversible sequel, even more so when it is secondary to a high incidence pathology such as acne. The main objective of this article is to review the existing valid evidence on the different treatment options and the association of these therapies to attenuate the scars caused by acne vulgaris. Literature review was used as a research methodology. In conclusion, the programming of the various parameters of the different types of therapies seems to play a definitive role in the final success of the treatment.